2020
DOI: 10.1136/bmjopen-2020-038283
|View full text |Cite
|
Sign up to set email alerts
|

Has the reporting quality of published randomised controlled trial protocols improved since the SPIRIT statement? A methodological study

Abstract: ObjectivesTo determine the reporting quality of published randomised controlled trial (RCT) protocols before and after the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) statement (2013), and any association with author, trial or journal factors.DesignMethodological study.Data sourcesMEDLINE, Embase and CENTRAL were electronically searched using optimised search strategies.Eligibility criteriaProtocols written for an RCT of living humans, published in full text in a peer-reviewed j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Given the various existing documentation that has been published to improve the quality and comprehensiveness of SPIRIT reporting in trial protocols, it is surprising that compliance is not higher. Recent research on trial protocol reporting has shown a significant improvement in the overall proportion of protocol items that are addressed since the SPIRIT guidance was published; however, this increase was only by approximately 9%, and several items were found to be less commonly reported [ 10 , 11 ]. Studies that have examined interventions to improve adherence to reporting guidelines in general have found many different types of interventions for different stages of the publication process [ 22 24 ].…”
Section: How Can Spirit Checklist Compliance Be Improved?mentioning
confidence: 99%
See 3 more Smart Citations
“…Given the various existing documentation that has been published to improve the quality and comprehensiveness of SPIRIT reporting in trial protocols, it is surprising that compliance is not higher. Recent research on trial protocol reporting has shown a significant improvement in the overall proportion of protocol items that are addressed since the SPIRIT guidance was published; however, this increase was only by approximately 9%, and several items were found to be less commonly reported [ 10 , 11 ]. Studies that have examined interventions to improve adherence to reporting guidelines in general have found many different types of interventions for different stages of the publication process [ 22 24 ].…”
Section: How Can Spirit Checklist Compliance Be Improved?mentioning
confidence: 99%
“…Although the checklist was published in 2013, as with many reporting checklists such as Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Consolidated Standards of Reporting Trials (CONSORT), the adherence and compliance among publications have seen only moderate improvement. A recent methodological study compared the overall proportion of checklist items adequately reported in RCT protocols published before and after the SPIRIT statement, respectively in 2012 and 2019 [ 10 ]. The investigators found an average of 57% of items were adequately reported in 2019 protocols, as compared with 48% in protocols from 2012 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for protocols (PRISMA-P) was developed in 2015 to improve the reporting quality of systematic reviews and metaanalysis protocols. 12 One study 13 showed that the reporting quality of protocols of clinical trials has improved by 8.8% since the publication of the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) 2013 statement. 14 To our knowledge, there are no widely agreed on guidelines or standards for how guideline protocols should be reported.…”
Section: Introductionmentioning
confidence: 99%